Innovation in the public sector in a small open economy-initial investigation of patent activity at the Czech universities - Petra Maresova; Ivan Soukal; Ruzena Stemberkova; Kamil Kuca (Journal of Innovation and Entrepreneurship, 2020)
For a successful economy, the interaction between research and its application in practice plays a key role. The aim of this paper is to analyze the institutional factors of patent activity at universities in the Czech Republic. The following five factors were selected for detailed investigation: budget from government, number of employees: professors, associate professor, and assistant professor, number of researchers and other employees, number of students (PhD, master, and bachelor), technology transfer workers. The patent activity analysis used methods of retrospective data analysis in the field of R&D activities, unstructured interviews, and statistical data processing. Following from the basic characteristics of the collected data, patent activity is related to the nature of universities, where technical universities are in leading positions in the monitored period of industrial-legal protection. However, the importance of encouraging innovation activity across all disciplines is crucial. The result of monitoring the dependency shows that a relationship of efficiencies and patent output is influenced by the size of a university. Secondly, there can be observed that technology transfer efficiency contributes more to the patent output that research staff efficiency.
Keywords: O12; O20; M10; H41; 650; Patent activities; Factors; Universities; Regression analysis; Czech Republic